Dual Mode MIMO-Beamforming Four Elements Array Antenna for Mobile Robot Communications at 5.6 GHz - Muhsin, Muhsin; Saharani, Aulia; Nurlaili, Afina Lina (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
Mobile robot communications are essential for robot teamwork. To enable communication between robots, reliable wireless communications must be deployed. Higher performance and capacity of communication are required. Multiple-input multiple-output (MIMO) and beamforming are important wireless communication technologies that use multiple antennas to improve communications performance and capacity. However, these two technologies have different requirements. MIMO requires the antenna element to be independent. While beamforming needs antennas to be coupled and fed by the same source. This paper proposes a dual-mode antenna for mobile robot communications at 5.6 GHz that supports both beamforming and MIMO. A single antenna consists of a planar dipole antenna arranged in a circular configuration. This antenna is then expanded to a four-element array antenna. Both MIMO and beamforming evaluations are performed. In MIMO mode, the BER performance is very similar to a non-correlated MIMO antenna. It is supported by the very low correlation between antennas below 0.01. Low coupling is also achieved below -16.5 dB. In beamforming mode, the proposed antenna achieves more than 8.6 dBi gain and good beam steering capability. It is supported by beam suppression with a 90° phase difference between the front and back direction. The proposed antenna performs well in both the MIMO and beamforming modes.